Compared prognostic impact of incident atrial fibrillation versus history of atrial fibrillation in patients with AMI: the FAST-MI programme. (25th November 2020) - Danchin, N; Fauchier, L; Marijon, E; Lavergne, T; Boveda, S; Martinet, M; Defaye, P; Piot, O; Puymirat, E; Bataille, V; Drouet, E; Ferrieres, J; et al.
Abstract: Background: History of atrial fibrillation (HxAF) and new onset atrial fibrillation (NOAF) at acute stage of MI are associated with poorer survival. Whether both entities carry an increased risk of stroke is uncertain. Using data from the FAST-MI 2010 and 2015 registries, we analysed the associations between HxAF and NOAF and risk of 3-year death, nonfatal stroke or combined death or stroke. Methods: The FAST-MI registries are nationwide French cohorts consecutively including AMI patients admitted over a 1-month period every 5 years. Baseline characteristics, acute management and medications at discharge are collected. Among 9460 patients with STEMI or NSTEMI, 610 (6.4%) had HxAF, and 626 (6.6%) developed NOAF. Main characteristics: Table 1 Overall, NOAF was associated with larger and more severe AMIs. Results: In hospital survivors, 3-year death was 8.6% in patients without AF, 23.2% in those with NOAF and 29.2% in those with HxAF. 3-year Kaplan-Meier rates of non-fatal stroke were 1.1%, 0.3% and 3.6%, respectively (Figure). Compared with no AF, NOAF was not associated with non-fatal stroke (Cox HR, 95% CI: 0.17, 0.02–1.21), while HxAF was (HR, 95% CI 2.04, 1.13–3.66, P=0.017). Risk of death or stroke was increased for both NOAF (HR, 95% CI 1.35, 1.10–1.65, P=0.004) and HxAF (HR 95% CI, 1.37, 1.14–1.65, P=0.001). Risk of all-cause death at 3 years was increased for NOAF (HR, 95% CI 1.32, 1.09–1.60) and HxAF (HR, 95% CI 1.30, 1.09–1.55). The results were concordant in patients not receiving oral anticoagulants at discharge. Conclusion: Both NOAF and HxAF are associated with increased risk of death at 3 years after AMI. NOAF, however, is not associated with an increased risk of non-fatal stroke. Funding Acknowledgement: Type of funding source: Other. Main funding source(s): Pharma companies